The Implementation of HACCP in Supporting Sustainability in the Food and Beverage Service Business - Narendra Duhita; Zeilla Nailurrahmi; Fauziyya Hafizh Muslim (Depertment of Hospitality, Politeknik Pariwisata NHI Bandung, 2025)
Purpose of the study: The aim of this study is to evaluate the impact of implementing the HACCP system on sustainability within the food and beverage service sector in Bandung, Indonesia, using the Triple Bottom Line (TBL) framework to explore the balance between profitability, social responsibility, and environmental sustainability. Design/methodology: The study utilizes a descriptive, qualitative approach, involving purposive sampling of operational managers, employees, and customers. Tools include interviews, surveys, and data triangulation. Software used for data analysis is adapted from Miles and Huberman’s framework, with a focus on the TBL theory Findings: The implementation of HACCP, personal hygiene, and environmental cleanliness contributes to food safety, enhances profitability by reducing food safety risks, and promotes sustainability by reducing waste and resource consumption, aligned with the Triple Bottom Line framework. Research limitations/Implications: This study is useful for businesses in the food and beverage service sector, particularly in Indonesia, and can benefit industries focused on food safety, sustainability, and corporate social responsibility within the fields of hospitality, tourism, and environmental management. Novelty/Originality of the study: This study advances existing knowledge by linking the implementation of HACCP with sustainability goals using the Triple Bottom Line framework, highlighting how food safety systems can contribute not only to consumer health but also to environmental sustainability and long-term business profitability in the food and beverage service industry.